SURFACE CURVATURE PARAMETERS IN, DETERMINING PAVEMENT PERFORMANC - Ames Halomoan, Paul
SURFACE CURVATURE PARAMETERS IN DETERMINING PAVEMENT PERFORMANCE, Halomoan, Paul Ames, i987, Program Sistem dan TeRnik Jalan Raya, Fakultas Pasca Sarjana Institut Teknologi Bandung. Pavement deflection and surface curvature readings arising from wheel loads can be employed for structural analysis, bearing capacity calculations, and estimations of the life expectancy of pavement systems. In order to assess surface curvature for a number of roads in the vicinity of Bandung, deflection testing was carried out over selected sections of road using a Benkelman Beam. The testing determined accurately the shape of the deflection bowl, resulting from the loading by a standard wheel load. Dynamic Cone Penetrometer (DCP) tests were also carried out on subbase layers and subgrade at selected points matching locations where Benkelman Beam testing was in progress. \' The deflection bowl readings were used to determine a best fit curve for the bowl and the minimum radii of curvature obtained, these values being used in a study of Surface Curvature Index (SCI), a parameter which has been used to signify weak areas of a pavement structure. The results are also used to establish whether the standard number of offset readings taken in deflection testing in Indonesia could adequately predict the minimum radius of curvature. Results, in general, were satisfactory and encouraging of further development. Maximum tensile strain values were also examined and compared against likely theoretical maximum values. Results showed that tensile strains developed under a standard wheel load on the road constructed to modern standards were within satisfactory limits, but these were exceeded at some locations of old roads constructed with pseudo-Telford bases. The DCP measured subgrade modulus values were compared with those calculated from the deflection test measurements using two-layer elastic theory. Comparisons were reasonable except for two sections of road where the apparent characteristics of the volcanic sub-soil produced unusually extensive deflection bowls